Polarisation and politicisation: the social media strategies of Indian political parties - Mahapatra, Sangeeta and Plagemann, Johannes (GIGA Focus Asien, 2019)
Ahead of the general election in April and May 2019, Indian political parties are using social media aggressively to propagate their ideology, mobilise public opinion, set policy agendas, and discredit detractors. Since the 2014 general election, India's two major political parties -the Bharatiya Janata Party, which currently leads the coalition government, and the Indian National Congress, the main opposition party- have invested heavily in digital political campaigning. Political parties use social media to directly and continuously engage with voters. More so than traditional media, social media can amplify and mobilise political opinions and reach out to even the remotest geographical areas. Social media's unique value is that it allows for both mass messaging and micro-targeting. Bolstered by grass-roots campaigning, it is immensely powerful in moulding public opinion both in India and beyond. While facilitating civic engagement for a more participatory democracy, social media is also misused for propaganda, hate speech, and disinformation campaigns, which can undermine the pluralistic foundations of Indian democracy. Today, successful political campaigns rest on the innovative employment of social media, a trend that has made voters increasingly invested in politics and parties. But it has also provided grist for political polarisation, particularly in heterogeneous societies such as India. Given this scenario, foreign policy observers should prepare for a more politicised and domestically contested conducting of Indian foreign affairs in future.
https://katalog.adlr.link/Record/finc-30-61811